Ministerial Decree No.430/2021 Promulgating The Executive Regulations of the Customs Law promulgating by law No. 207/2020 = قرار وزاري رقم 430 لسنة 2021 بإصدار اللائحة التنفيذية لقانون الجمارك الصادر بالقانون رقم 207 لسنة 2020 - EGYPT (2025)
Part-1: Definitions Customs authority and its officers Customs control procedures for protection of intellectual property rights (IPR) Boundary of customs control Authority's officers Part-2: Chapter- 1: Chapter - 2: Chapter - 3: 9. 6. Customs tax and service charge Part-3: Chapter - 1: Chapter - 2: Chapter- 3: Customs tax Customs tax base Service charge 15 97 Customs exemptions Special customs regimes Transit goods Customs bonded warehouses (CBW) Temporary storage Free zones Economic zones of special nature Duty-free shops Temporary admission Temporary release Tax refund Part -5: Chapter- 1: Chapter-2: Chapter - 3: Chapter - 4: Chapter- 5: Chapter - 6: Chapter-7: Chapter - 8: Chapter - 9: 43 65 09 19 Customs procedures Advance cargo information (ACI) Pre-clearance 88 :9 -u 88 16 Chapter - 1: Chapter - 2: Chapter - 3: Chapter - 4: Chapter- 5: Chapter- 6: Chapter - 7: Chapter- 8: S6 101 Cargo transport Cargo manifest The customs declaration Customs brokers Inspection and withdrawal of goods Customs formalities on imported and exported goods 105 112 115 120 Part-7: Appeals and settlement of customs disputes 141 Part-8: Procedures of the sale goods 146 Part-9: Offences and penalties 151 Concluding provisions Exchange of electronically-secured information and data Risk management system Transport of goods using different means of transport Authorized economic operator (AEO) Part - 10: 155 Chapter-1: Chapter - 2: Chapter - 3: Chapter-4: Chapter-5: Chapter-6: 155 091 suod kia 691 173 Annex (1): Wages of the works performed by the Authority's officers in favor of the parties concerned in other than official working hours or outside the customs house 174 Annex (2): Services charges LLE Expenses of storing the goods at the warehouses, bonded warehouses and yards operated by the authority Annex (3): 181 Annex (4): Prices of forms and publications 182 Annex (5): Nafeza platform service charges 183 :(9) annex Customs clearance license forms 184